2019
DOI: 10.5194/amt-2019-275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical discrimination of the particulate and gas phases of miniCAST exhausts using a two-filter collection method

Abstract: Abstract. Combustion of hydrocarbons produces both particulate and gas phase emissions responsible for major impacts on atmospheric chemistry and human health. Ascertaining the impact of these emissions, especially on human health, is not straightforward because of our relatively poor knowledge of how chemical compounds are partitioned between the particle and gas phases. Accordingly, we propose to couple a two-filter sampling method with a multi-technique analytical approach to fully characterize the particul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Consequently, we characterized the nature of the organics making up the samples' surfaces using mass spectrometry techniques. Our surface analyses clearly highlighted that the 'organic content' referred to in bulk analyses 53,56,84 can be identified as being a mixture of PAHs. However, it is also clear that different features appear for the two CAST soot type of samples (Figure 8), where…”
Section: Influence Of Sample Surface Composition the Chemical Composition Of Propane Sootmentioning
confidence: 77%
See 3 more Smart Citations
“…Consequently, we characterized the nature of the organics making up the samples' surfaces using mass spectrometry techniques. Our surface analyses clearly highlighted that the 'organic content' referred to in bulk analyses 53,56,84 can be identified as being a mixture of PAHs. However, it is also clear that different features appear for the two CAST soot type of samples (Figure 8), where…”
Section: Influence Of Sample Surface Composition the Chemical Composition Of Propane Sootmentioning
confidence: 77%
“…The surface chemical composition of soot samples was probed by two mass spectrometry techniques: two-step laser mass spectrometry (L2MS) and secondary ion mass spectrometry (SIMS). 55,56 The custom-built L2MS apparatus has been described in detail elsewhere. 57−60 Briefly, the collimated (2 mm diameter) beam of a Nd:YAG laser (Continuum Minilite II, 5 ns, 532 nm, 10 Hz) irradiates the surface of the sample, placed under vacuum (10 −8 mbar) on a cryogenic stage.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CS efficiency was assessed by measuring the volatile organic fraction. An original two-filter system (Ngo et al, 2020) was developed to sample simultaneously the gas phase and the particulate matter from the exhaust, yet on separate substrates. Mass spectrometry analyses showed that the catalytic stripper effectively removed the organic content regardless of the phase (gas or particles), as demonstrated by a drastic reduction (more than one order of magnitude) of the recorded total ion count.…”
Section: Pems4nanomentioning
confidence: 99%